Fostering culture of care for early career researchers—Building a trustful environment: Insights from a German perspective - Fernando Gonzalez-Uarquin; Fabienne Ferrara; Nadine Baumgart; Jan Baumgart; Sabine Juliane Bischoff (PLoS ONE, 2025)
Early-career researchers (ECRs) play a key role in conducting animal experiments in academic research. However, they face considerable challenges, including poor working conditions, and inadequate strategies for managing distress. These difficulties are often amplified in animal research, where a lack of consensus on the 3Rs (replacement, reduction, and refinement), challenges to navigate complex regulations and ethical dilemmas can further complicate the situation. These challenges not only jeopardize the well-being of both animals and researchers, but also undermine the quality of scientific work, potentially driving ECRs out of academia. This paper explores the relationship between 3Rs training, communication, and stress-coping mechanisms used by ECRs in Germany and provides recommendations to address the challenges. To that end, we employed a dual-method approach: surveying ECRs to gather their perspectives on working with laboratory animals, communication challenges, and stress management, while also conducting a workshop to exchange insights with experienced professionals who engage with ECRs in their daily roles. Our results highlight the many difficulties faced by ECRs working on animal experiments, which range from organizational challenges to the practical implementation of the experiments. These insights emphasize the need for a holistic strategy that includes direct engagement with ECRs and the development of policies focused on their overall well-being. Our recommendations advocate for improved communication strategies, recognition of cultural differences, implementation of peer coaching and mentoring programs, and strengthening institutional support systems particularly with regard to the conduct of animal experiments. To conclude, this research calls for a transformative shift towards a more supportive and inclusive environment for ECRs, harmonizing scientific progress with ethical standards.